Immunotoxic properties of 5 % suspension of Kokcidon - D. S. Poselov; M. V. Arisov (Российский паразитологический журнал, 2016)
Immunotoxic properties of 5 % suspension of kokcidon in two tests are stud-ied. By results of reaction of hypersensitivity of the slowed-down type the reaction index at the animals receiving a preparation in a therapeutic dose of 0,4 ml/kg, has made 11,46, at the animals receiving a 10 times increased dose – 11,31, and at an-imals of control group – 14,26 that allows to draw a conclusion on lack of oppress-ing effect of 5 % suspension kokcidon on the T-cellular link of immune system. A single skin application of tested drug in a therapeutic and tenfold increased thera-peutic doses doesn't cause changes of intensity of antibody production against a thymus-dependent antigen. The index of action of a preparation in both doses made 0,98. Reaction of gemagglyutination didn't reveal negative influence of a prepara-tion on the humoral immune answer.